Artificial intelligence in operational applications of railway infrastructure manager - Šrámek, Přemysl; Široký, Jaromír; Vojtek, Martin (České vysoké učení technické v Praze, 2023)
The main goal of this article is to present the possibility of using artificial intelligence in operational application of railway infrastructure manager. Railway 4.0 can be controlled fully digitally – operational applications based on the artificial intelligence can optimize the technology of railway traffic control. Thereafter, a wide range of equipment could be controlled by application through a secure interface.
Umělá inteligence v provozních aplikacích správce železniční infrastruktury
Keywords: Artificial intelligence; operational applications; railway traffic control; railway 4.0.; Umělá inteligence, provozní aplikace; řízení železničního provozu; železnice 4.0.